Ethics in Ethnobiology Publication - James R. Welch (Ethnobiology Letters, 2012)
With the recent multiplication of traditional and electronic venues for publishing in ethnobiology, the social sciences, the life sciences, and related fields, it is increasingly important that authors practice self-diligence to ensure that the contents of their publications meet criteria of veracity and ethical soundness. Although the peer-review process encourages high standards, it is an insufficient means for verifying the ethical worthiness of most publications. The ethical merits of published research derive from a cumulative process including formulating a research design, obtaining permissions, collecting and analyzing data, and finally composing and submitting a manuscript. Unfortunately, there is no failsafe ethical gatekeeper at any stage of the process. The importance of ethical publishing is all the more important in the field of ethnobiology, as professionals in the field  often cross the intellectual and methodological boundaries between disciplines, and their research often involves multiple stakeholders in widespread jurisdictions.